The Reception of International Human Rights Law in Charter Litigation: “Not a Box of Chocolates” But You Still “Never Know What You’re Gonna Get” - Lantz, Karinne (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2026)
This article explores the reception of international human rights law (IHRL) in Canada. Focusing on the Charter context, it demonstrates that how IHRL applies in Canada continues to lack clarity despite repeated (and recent) efforts by the Supreme Court of Canada to provide it. This article argues that this lack of clarity is an important matter for the Court to address, particularly as IHRL is increasingly being invoked before courts and other tribunals around the world. It argues that the Court should adopt a methodology that: (i) endorses the “Dickson Doctrine,” according to which the “minimum protection approach” is robustly applied for international human rights that are binding upon Canada, while relevant, non-binding international human rights are considered for their persuasive value when interpreting relevant Charter rights; and (ii) uses international legal principles to interpret IHRL and to determine the interpretive weight to afford to international legal materials. In doing so, it is crucial for the Supreme Court to finally heed long-standing calls to dispel uncertainty by clearly explaining its methodology and reconciling its jurisprudence. In addition to being consistent with existing jurisprudence, this approach would assist with narrowing the gap between Canada’s international and domestic human rights obligations; acknowledge the binding nature of Canada’s IHRL obligations; respect concerns for separation and divisions of powers; and, ultimately, contribute to maintaining the rule of law while providing additional clarity regarding the scope of fundamental rights and freedoms in Canada.